2006
DOI: 10.1097/01.rti.0000203636.43758.62
|View full text |Cite
|
Sign up to set email alerts
|

Complications Following the Ross Procedure

Abstract: Aortic valve replacement with a pulmonary autograft (ie, Ross procedure) is a technique used in selected cases for the treatment of aortic valve disease. Aware of reports describing chronic complications after the Ross procedure such as aortic insufficiency, right ventricular outlet obstruction, aortic autograft dilatation, and pulmonary allograft stenosis, cardiac magnetic resonance imaging (MRI) was performed in individuals who had a previous Ross procedure (range 2 to 10 years earlier) to determine if these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Any jet formation should be visualized by cine imaging and quantified by jet velocity mapping, and regurgitation measured by through-plane velocity mapping. 51,52 The autograft valve in the aortic position should also be assessed for possible dilatation and regurgitation particularly in the second decade after operation. 53 Possible sub-valvular pseudo-aneurym formation at the proximal suture line should be sought.…”
Section: Specific Indicationsmentioning
confidence: 99%
“…Any jet formation should be visualized by cine imaging and quantified by jet velocity mapping, and regurgitation measured by through-plane velocity mapping. 51,52 The autograft valve in the aortic position should also be assessed for possible dilatation and regurgitation particularly in the second decade after operation. 53 Possible sub-valvular pseudo-aneurym formation at the proximal suture line should be sought.…”
Section: Specific Indicationsmentioning
confidence: 99%
“…Grotenhuis et al [6] have shown that MRI-derived measurements of aortic root diameter, aortic root distensibility, and aortic regurgitation correlate with LV dysfunction in patients after the Ross procedure. Crowe et al [7] have shown right-heart complications of the Ross procedure using MRI; these include pulmonary valve stenosis (Fig. 2), pulmonary regurgitation, main pulmonary artery obstruction, and RV dysfunction.…”
Section: Mr Angiography For Measurement Of Pulmonary Circulationmentioning
confidence: 99%